Rezonans a rejestry głosowe - Danel, Renata (Logopedia Silesiana, 2012)
Resonance and voice registrations Resonance and voice registrations are one of the important factors of vocal technique. They include the wide range of issues which recognition, and skilful usage causes full and conscious voice operation. Working out proper skills of using voice resonance with a reference to free conscious operation of voice registration is not only a subject of long term process of learning to sing, but also is the center of attention during continuous work on the voice of every vocalist. Definitions of notions, division of resonance chambers and voice registrations their functions and a role and dependence in the process of phonation – there subject of the work.